2010
DOI: 10.1364/ol.35.001771
|View full text |Cite
|
Sign up to set email alerts
|

Soliton explosion control by higher-order effects

Abstract: We numerically study the impact of self-frequency shift, self-steepening, and third-order dispersion on the erupting soliton solutions of the quintic complex Ginzburg-Landau equation. We find that the pulse explosions can be completely eliminated if these higher-order effects are properly conjugated two by two. In particular, we observe that positive third-order dispersion can compensate the self-frequency shift effect, whereas negative third-order dispersion can compensate the self-steepening effect. A stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 17 publications
1
35
0
Order By: Relevance
“…The erupting solitons have been found numerically [12] on a relatively large region of the CGLE parameter space, and were experimentally observed in passively mode-locked lasers [14]. Recently, the eruptions were shown to change or even cancel by the introduction of one or more additional terms in the CGLE [15][16][17][18]. In fact, in [18] we have shown that the intrapulse Raman scattering (IRS), if sufficiently strong, may stabilize the propagation of the single pulse on the eruption parameter region, thus eliminating the eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…The erupting solitons have been found numerically [12] on a relatively large region of the CGLE parameter space, and were experimentally observed in passively mode-locked lasers [14]. Recently, the eruptions were shown to change or even cancel by the introduction of one or more additional terms in the CGLE [15][16][17][18]. In fact, in [18] we have shown that the intrapulse Raman scattering (IRS), if sufficiently strong, may stabilize the propagation of the single pulse on the eruption parameter region, thus eliminating the eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, terms similar to intrapulse Raman scattering (IRS) and selfsteepening (SS) were used by Tian et al [18] to control the eruptions, thus obtaining fixed shape soliton propagation with nonzero velocity. Also, more recently, Latas et al [19] obtained asymmetric eruptions or complete elimination of eruptions by adding IRS, SS and third order dispersion to the CGLE.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, from all of these, the only stable pulse is the high amplitude solution allowed when R r ̸ = 0 in region 1, but for ϵ that obeys condition (6). In some cases, as is the case S i = 0, the condition (6) reduces to ϵ < ϵ max = β and the existence of a finite region with stable solitons implies that ϵ min < ϵ max , which imposes an additional restriction on the coefficients of (1), they will exist as long as |R r | < 5 12 β…”
Section: (Region 5)mentioning
confidence: 99%
“…However, it has been recently shown that the inclusion in the CGLE of a term that, in optics, models the delayed Raman scattering, allows the existence of stable solutions in a parameter region where the background is also stable [4]. Note that this higher order term has also been associated with the stabilization of erupting solitons of the quintic CGLE [5][6][7].…”
Section: Introductionmentioning
confidence: 99%